Analysis Of The Relationship Between Mother's Characteristics And Motives For Food Choices For Children - Baiq Fitria Rahmiati; Wayan Canny Naktiany; Wiwin Lastyana; Novia Zuriatun Solehah; Junendri Ardian (Poltekkes Kemenkes Mataram, 2022)
Background. Nutritional problems in Indonesia are still dominated by malnutrition in children. This problem is caused not only due to lack of food but also influenced by the characteristics of the mother because the mother plays a vital role in fulfilling children's nutrition. The purpose of this study is to analyze the correlation between maternal traits and food choice motives. Research Methods. The research respondents were 50 people who were selected randomly (simple random sampling). This study uses quantitative methods supported by qualitative data. Data collection techniques used questionnaires to collect quantitative data and in-depth interviews to collect qualitative data. Quantitative data will be analyzed using the Spearman correlation test with SPSS software. The qualitative data will be presented in the form of a narrative that is used to support quantitative data. Research Result. Based on the Spearman correlation test, it was found that the level of knowledge had no significant effect on the mother's food choice motive with p value 0.056 (> 0.05), and there is no correlation between education and maternal food choice motives with a p-value of 0.422 (> 0.05). Conclusion. The results show no influence between the mother's characteristics and food choice motives (p-value > 0.05).